Sosialisasi Pencegahan Bahaya Rabies dan Penaggulangan Pernikahan Anak di Usia Dini di Kabupaten Bone - Amali, Febrian Zulfiansyah; Dandi Dandi; Mutiara Mutiara; Eva Eva; Mutiara Aprilia; Ridwan Ridwan; Muh. Amin Amir; Rifki Kurniawan; Hasriliandi Halim (Universitas 45 Surabaya, 2024)
Rabies can attack all types of warm-blooded animals and humans. Symptoms of rabies in humans usually begin with fever, headache, difficulty swallowing, fear of water, sensitivity to wind and sound stimuli and end in death. Control of rabies is generally done by vaccination and elimination of stray/wild dogs, in addition to socialization programs and supervision of rabies-transmitting animal traffic (HPR). While in early marriage, it has a negative impact on teenagers and when living in a family, early marriage can be caused by several factors, namely, social factors, economic factors, educational factors. Prevention of early marriage can be done by providing education about the dangers and impacts of early marriage